ACUTE MACULAR EDEMA WITH SEROUS RETINAL DETACHMENT AFTER CATARACT SURGERY IN A VITRECTOMIZED EYE: A CASE REPORT. Issue Volume 15:Issues 6(2021) (November 2021) - Bryan, Eric A.; Cruz-Iñigo, Yousef J.; Brems, Robert N.; Bryan, J. Shepard
Abstract : Purpose: To present the first case of acute macular edema with serous retinal detachment after cataract surgery in a vitrectomized eye. Methods: A 63-year-old female patient, with history of pars plana vitrectomy and epiretinal membrane removal, underwent uneventful phacoemulsification surgery with injection of standard intracameral dose of cefuroxime (1 mg/0.1 mL of solution) at the end of the procedure. Results: First day after cataract surgery, visual acuity did not correlate with anterior segment findings, and funduscopic eye examination revealed acute macular edema with serous retinal detachment, which was confirmed by spectral domain optical coherence tomography. Fluorescein angiography showed no retinal or choroidal hyperpermeability. At 2-week follow-up visit, visual acuity had significantly improved, and there was complete resolution of macular edema and subretinal fluid. Conclusion: The current case suggests that acute macular edema with serous retinal detachment after cataract surgery with standard cefuroxime prophylaxis can occur even in vitrectomized eyes. A high level of suspicious is needed when visual acuity does not correlate with anterior segment findings immediately after cataract surgery. Similar to reports from nonvitrectomized eyes, visual prognosis was favorable. Abstract : The authors report a case of acute macular edema with serous retinal detachment after cataract surgery with standard intracameral cefuroxime prophylaxis in a vitrectomized eye.